The Influence of Trust and Security on Buying Interest Moderated Service Quality at Bata Shoe Stores during the Pandemic - Koerniawan Hidajat; Fais Datul Fidad Nurul Islam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Changes in the lifestyle of today's society, for entrepreneurs and retail businesses, namely providing quality service and especially trust in shopping. This study aims to examine and discuss the effect of trust on buying interest moderated by service quality at a supermarket in a sunter mall. This approach uses casual associative quantitative data and data obtained through questionnaires. The results of this study indicate that entering the new normal is a step for consumers to shop during the pandemic. The sample of brick shoes consumers is 106 people. The analysis uses a structural model that is processed by SMARTPLS 3.0 software.